2019
DOI: 10.1136/bjsports-2019-100731
|View full text |Cite
|
Sign up to set email alerts
|

Mental health symptoms and disorders in Paralympic athletes: a narrative review

Abstract: ObjectivesThis narrative review summarises the literature on the mental health of Paralympic athletes, explores possible reasons for the paucity of research in this area and suggests directions for future research.MethodsA systematic search of PubMed, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, SPORTDiscus, Scopus, and Cochrane databases was conducted using search terms related to disability, sport and mental health.ResultsThe search yielded 665 publications. Of these, 129 were duplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 35 publications
(48 reference statements)
3
67
1
Order By: Relevance
“…Research has shown that sport participation enhanced self and social acceptance, identity development, and quality of life. Paralympians did not view themselves as having lost something, as being disabled, nor as supercrips, which support the Affirmation Model of Disability (Pack et al, 2017 ; Swartz et al, 2019 ). In contrast, Huang and Brittain ( 2006 ) reported that most Paralympians assigned their impairment as their “master identity status” instead of AI, which follows the medical model.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…Research has shown that sport participation enhanced self and social acceptance, identity development, and quality of life. Paralympians did not view themselves as having lost something, as being disabled, nor as supercrips, which support the Affirmation Model of Disability (Pack et al, 2017 ; Swartz et al, 2019 ). In contrast, Huang and Brittain ( 2006 ) reported that most Paralympians assigned their impairment as their “master identity status” instead of AI, which follows the medical model.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Paralympic-level athletes already face challenges including overtraining and injury, normalized pain, and health hazards (Fagher et al, 2016 ). Moreover, they continue to struggle with external barriers such as lack of sufficient adaptive sport facilities, as well as logistical hurdles in travel to competition sites (Swartz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…38 The APSQ is a brief, self-report rating scale specific to the sport context and relying on 10 items (eg, 'During the past 4 weeks, I could not stop worrying about injury or my performance') scored on a 5-point scale (from 'none of the time' (1) to 'all of the time' (5)). 37 A total score ranging from 10 to 50 is calculated by summing the answers on the 10 items, with a score of 17 or more indicating an elevated or high risk for psychological distress. 38 39 The APSQ has been validated in male and female athletes (area under curve value >0.90).…”
Section: The Sport Mental Health Assessment Toolmentioning
confidence: 99%
“…The lack of support from support staff in certain situations, such as following poor race performances, was also raised. Elite para-athletes can experience both sport and disability-specific stressors which can affect wellbeing and performance, with the process of reclassification being particularly traumatic and isolating, further demonstrating the need for appropriate mental health support from British para-swimming staff [2,14,[66][67][68].…”
Section: British Para-swimmingmentioning
confidence: 99%
“…The Paralympic Games is regarded as the pinnacle of para-sport and is the second largest global multi-sport event [1][2][3][4]. The profile and popularity of the Games has increased considerably since inception, with over 4000 athletes participating at the Rio 2016 Paralympic Games [5].…”
Section: Introductionmentioning
confidence: 99%